Pengaruh Depresiasi Nilai Tukar Rupiah terhadap Return Saham Bank BUMN (HIMBARA) yang Terdaftar di Bursa Efek Indonesia Periode April–Juli 2026 - Kurniawan Firdaus (Jurnal Kendali Akuntansi, 2026)
This paper examines the extent to which rupiah depreciation affected share-price returns among Indonesia's state-owned (HIMBARA) banking group on the Indonesia Stock Exchange over the four months from April through July 2026, a window marked by sustained pressure on the local currency as the US dollar index climbed. Using a quantitative causal-associative design, daily observations for five HIMBARA lenders (BBNI, BBRI, BBTN, BMRI, and BRIS) were matched against Bank Indonesia's JISDOR benchmark rate, producing 375 panel data points in total. Following the Chow and Hausman procedures, the Common Effect Model (CEM) combined with White-period robust standard errors emerged as the specification best suited to the data. The estimation results reveal a negative, statistically significant relationship between currency depreciation and HIMBARA share returns (coefficient = -3.469960; p = 0.0000), confirming the hypothesis and echoing signaling theory's premise that investors treat a weakening currency as an adverse cue about a bank's outlook. Roughly 15.60 percent of the variation in returns is captured by the model, implying that other fundamental and macroeconomic drivers account for the remainder. Findings offer guidance for investors, bank managers, and regulators looking to manage exchange-rate exposure within the banking industry.